The effect of increased regiment activities on the health condition of cadets - Nadiza Lediwara; Sembada Denrineksa Bimorogo; Aulia Khamas Heikmakhtiar; Azzam Amar Ma’ruf; Daffa Mahdy Brata (Fakultas Teknik dan Teknologi Pertahanan, Universitas Pertahanan Republik Indonesia, 2026)
This study aims to analyze the effect of increased regiment activities on the health conditions of student cadets at the Republic of Indonesia Defense University (UNHAN RI). Regiment activities, which include physical training, discipline building, and mental development, are considered to influence both physical and mental health aspects of cadets. This study employed a quantitative comparative design using a paired sample approach to examine changes in health conditions before and after an increase in regiment activity intensity. Data were collected using a structured questionnaire and analyzed using a paired sample t-test. The results indicate a statistically significant difference in cadets’ health conditions before and after the increase in regiment activity intensity, as indicated by a p-value of 1.029 × 10⁻⁶ (p < 0.05). These findings provide empirical evidence of the impact of regiment activity intensity on cadet health and highlight the importance of managing training intensity to support optimal health outcomes in military-based educational institutions.